Spaces of geographical thought : deconstructing human geography's binaries - Cloke, Paul J.; Johnston, Ron (Society and space series., 2005)
Spaces of Geographical Thought examines key ideas - like space and place - which inform the geographic imagination. The text: discusses the core conceptual vocabulary of human geography: agency: structure; state: society; culture: economy; space: place; black: white; man: woman; nature: culture; local: global; and time: space; explains the significance of these binaries in the constitution of geographic thought; and shows how many of these binaries have been interrogated and re-imagined in more recent geographical thinking.